624 Healthy night in coimbra: primary prevention project in educational context. (1st September 2016) - Sola, Filipa; Simões, Paulo; Fernandes, Alexandre; Redondo, João
Abstract : Background: Night recreation plays an important role for young people but it has, sometimes, an intrinsic association to risk factors in areas such as sexuality, violence, road driving and consumption of alcohol or other substances. The influence of these risk behaviours in health status and life quality of young people has been widely documented in literature; documentation, monitorization and intervention in these behaviours has been considered by healthcare organisations as a public health priority. A survey conducted by European Institute of Studies on Prevention, Portugal (Coimbra, 2014), reports that today there is more violence and aggression in nightlife (60%), more cases of intoxication (70%), higher consumption of illegal drugs (43%) and sex under the influence of alcohol (65%). Methods: Sensibilization activities, on the scope of primary prevention, aimed for students from secondary schools (aged between 14 and 18), with emphasis on the following topics: consumption of alcohol and other psychoactive substances, violence, sexual risk behaviour and night road accidents. Sample: 235 students, 12 classes. A questionnaire was applied at the beginning of the second scholar period in order to characterise and understand the behaviours of the students and in the end of the third scholar period in order to assess the impact of our intervention. Results: We found that majority of the students increased knowledge in the addressed thematics. This methodology enables to introduce a new narrative on youngsters and developing a new perception of these thematics. Conclusions: Focusing the prevention idea and considering the premature beginning of risky behaviour, it is essential the intervention at younger ages, privileging the school context, which will be enhanced by the multidisciplinary and multisectoral network approach. We believe that early investment in these problematics represents an additional contribution to the promotion of healthy nights and safe communities.